2021
DOI: 10.1017/s0305000921000349
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prominence cues in 7- to 10-year-olds’ pronoun resolution: Disentangling order of mention, grammatical role, and semantic role

Abstract: In two visual world experiments we disentangled the influence of order of mention (first vs. second mention), grammatical role (subject vs object), and semantic role (proto-agent vs proto-patient) on 7- to 10-year-olds’ real-time interpretation of German pronouns. Children listened to SVO or OVS sentences containing active accusative verbs (küssen “to kiss”) in Experiment 1 (N = 72), or dative object-experiencer verbs (gefallen “to like”) in Experiment 2 (N = 64). This was followed by the personal pronoun er o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Therefore, prosody is simply not as stable of a cue for these children, so may be activated relatively less than for adults. Indeed, this fits previous work showing that young children do not initially use cues in the same way as adults ( Pyykkönen et al, 2010 ; Järvikivi et al, 2014 ; Goodrich Smith and Hudson Kam, 2015 ; Blything et al, 2021 ). The overall extent to which individual children resembled adults is likely dependent on a number of factors, ranging from whether they have the required language experience and developed the same robust preferences for established cues (e.g., subjecthood), as well as the processing skills required to appropriately activate and suppress multiple cues ( Järvikivi et al, 2014 ; Hartshorne et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, prosody is simply not as stable of a cue for these children, so may be activated relatively less than for adults. Indeed, this fits previous work showing that young children do not initially use cues in the same way as adults ( Pyykkönen et al, 2010 ; Järvikivi et al, 2014 ; Goodrich Smith and Hudson Kam, 2015 ; Blything et al, 2021 ). The overall extent to which individual children resembled adults is likely dependent on a number of factors, ranging from whether they have the required language experience and developed the same robust preferences for established cues (e.g., subjecthood), as well as the processing skills required to appropriately activate and suppress multiple cues ( Järvikivi et al, 2014 ; Hartshorne et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…A misalignment of cues may also explain why, unlike adults, prosody did not display a clear effect on children in object focus conditions. In these conditions, prosody was misaligned against established cues (subjectivity, first mention, and agentivity) and, compared to adults, children’s interpretive preferences are weakened by misaligned cues to a greater extent ( Blything et al, 2021 ). Related, whilst sensitivity to linguistic functions of prosodic focus marking starts to appear between 3 and 6 years of age, it is still developing during this age window ( Moore et al, 1993 ; Wells et al, 2004 ; Arnhold et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If order of mention affects the subject preference, we expect more subject choices in SVO order than in OVS order, and more object choices in OVS than in SVO order. As several studies found that referent preferences can be clearer when several effects combine (e.g., Blything et al., 2021; Kaiser & Trueswell, 2008), it is also possible that the subjecthood effect is modulated by information structure and/or word order.…”
Section: Current Studymentioning
confidence: 99%
“…In order to disentangle grammatical role (subject vs. object) and linear order (first‐ vs. second‐mention), previous research has often investigated pronoun resolution in languages with flexible word order, such as German and Finnish (Blything, Iraola Azpiroz, Allen, Hert, & Järvikivi, 2021; Bouma & Hopp, 2006; Järvikivi, van Gompel, Hyönä, & Bertram, 2005; Järvikivi, van Gompel, & Hyönä, 2017; Kaiser, 2011; Kaiser & Trueswell, 2008; Sauermann & Gagarina, 2017; Schumacher, Dangl, & Uzun, 2016; Schumacher et al., 2017).…”
Section: Introductionmentioning
confidence: 99%